Corrosion analysis - Dornbusch, Michael (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
"The book gives an overview on all relevant electrochemical and spectroscopic methods used in corrosion research. In addition to helping the reader choose the accurate method for a particular corrosion aspect, the various methods are correlated with industrial test methods for both the corrosion on metals (steel, zinc coated steel and aluminum) and the corrosion on coated metals (organic coatings and pre-treatments)"--
Basics -- Electrochemical methods -- Spectroscopic methods -- Investigation of the corrosion rate.
"A science publishers book."
OCLC-licensed vendor bibliographic record.
Keywords: Corrosion and anti-corrosives.; Protective coatings; TECHNOLOGY & ENGINEERING / Engineering (General); TECHNOLOGY & ENGINEERING / Reference; SCIENCE / Chemistry / Industrial & Technical; SCIENCE / Spectroscopy & Spectrum Analysis; TECHNOLOGY / Material Science